(untitled) (Al-Academy, 2022)
The art of theater penetrated various scientific and human fields, as well as touching the facts and events surrounding it, and scientific innovations had a wide field, so it adopted feedback in interactive theater performances, especially the theater of the oppressed. Then came the indicators that resulted from the theoretical framework for the formation of the tool by which the research sample is analyzed, and then the chapter concluded with previous studies. As for the third chapter, it involved the research procedures, and through the research tool and the research method, and by selecting the intentional sample, the sample represented by a play (the story of Shahrour) was analyzed. As for the fourth chapter, it included the results of the research, and the chapter also contained conclusions and a set of recommendations and proposals, and it was proven by the sources and references